2022
DOI: 10.2174/1573406417666210304100830
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Some Novel Benzimidazole Derivatives as Anticancer Agent and Evaluation for CDK2 Inhibition Activity

Abstract: Background: Thiobezimidazoles reveal various pharmacological activities due to similarities with many natural and synthetic molecules, they can easily interact with biomolecules of living systems. Objective: A series of substituted 2-thiobezimidazoles has been synthesized .Twelve final compounds were screened for in vitro anti-cancer activities against sixty different cell-lines. Methods: The spectral data of the synthesized compounds were characterized. Docking study for active anticancer compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The literature survey revealed that the benzimidazole derivatives have been extensively investigated as potential anticancer agents, and these benzimidazole derivatives exhibit anticancer effects through different mechanisms of action such as intercalating mode of action (DNA binding), nonintercalating mode of action (topoisomerases inhibition), DNA alkylation (DNA cleavage), acting on enzyme antimetabolites [DihydrofolateReductase (DHFR) inhibition], sirtuin inhibition (SIrt1 and SIrt2 inhibition), acting on structural proteins (tubulin protein inhibition), and protein kinase inhibition. …”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The literature survey revealed that the benzimidazole derivatives have been extensively investigated as potential anticancer agents, and these benzimidazole derivatives exhibit anticancer effects through different mechanisms of action such as intercalating mode of action (DNA binding), nonintercalating mode of action (topoisomerases inhibition), DNA alkylation (DNA cleavage), acting on enzyme antimetabolites [DihydrofolateReductase (DHFR) inhibition], sirtuin inhibition (SIrt1 and SIrt2 inhibition), acting on structural proteins (tubulin protein inhibition), and protein kinase inhibition. …”
Section: Introductionmentioning
confidence: 99%
“…NMR spectra of intermediates and final compounds 2, 3a, 3b, 3c, 4a, 4b, 4c, and TJ01−TJ15;13 C NMR spectra of the final compounds TJ01−TJ15; HRMS spectra of the final compounds TJ01−TJ15; LC−MS spectra of intermediates and final compounds 2, 3a, 3b, 3c, 4a, 4b, 4c, and TJ01−TJ15; FT-IR spectra of the final compounds TJ01−TJ15 (PDF) ■ AUTHOR INFORMATION Corresponding Authors…”
mentioning
confidence: 99%
See 3 more Smart Citations